2006
DOI: 10.1128/jb.188.7.2735-2739.2006
|View full text |Cite
|
Sign up to set email alerts
|

Altering the Length of the Lipopolysaccharide O Antigen Has an Impact on the Interaction ofSalmonella entericaSerovar Typhimurium with Macrophages and Complement

Abstract: A panel of isogenic Salmonella enterica serovar Typhimurium strains that vary only in the length of the O antigen was constructed through complementation of a wzz double mutant (displaying unregulated O-antigen length) with one of two homologous (wzz ST and wzz fepE ) or three heterologous (wzz O139 of Vibrio cholerae and wzz SF and wzz pHS-2 of Shigella flexneri) wzz genes. Each gene was functional in the S. enterica serovar Typhimurium host and specified production of O-antigen polymers with lengths typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 163 publications
(145 citation statements)
references
References 34 publications
2
140
2
1
Order By: Relevance
“…typhimurium LPS is also a major virulence factor with the length of the O-antigen contributing to survival in the host (40,55) and has been shown to play a role in adherence (56). We found that host blood group glycans could inhibit the association of S. typhimurium and Caco-2 cells when used at 10× the K D of the LPS:glycan interaction with 50% decreases in adherence noted.…”
Section: Discussionmentioning
confidence: 73%
“…typhimurium LPS is also a major virulence factor with the length of the O-antigen contributing to survival in the host (40,55) and has been shown to play a role in adherence (56). We found that host blood group glycans could inhibit the association of S. typhimurium and Caco-2 cells when used at 10× the K D of the LPS:glycan interaction with 50% decreases in adherence noted.…”
Section: Discussionmentioning
confidence: 73%
“…Regulation of surface polysaccharide length is an important adaptation that leads to optimal survival and virulence of pathogens [6][7][8]. During LPS Oag biosynthesis, Wzz proteins control Oag modal length distribution through two proposed mechanisms: as a molecular timer of Oag polymerization [9] or in an organizational manner to determine the crucial ratio of the polymerase Wzy to the Oag ligase WaaL [10].…”
Section: Wzy-dependent Polysaccharide Biosynthesismentioning
confidence: 99%
“…Additionally, the PCP1 group is divided into PCP1a and PCP1b, distinguishing the WzzB proteins (PCP1a) that operate on Oag from the WzzE proteins (PCP1b) that regulate the length of ECA [1]. The most striking effects on polysaccharide length have been visualized for the PCP1a proteins in Oag biosynthesis because Oag ladders can be resolved by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) such that the number of individual sugar repeat units can be counted, thus, enabling subtle differences in the degree of polymerization to be distinguished [7]. By contrast, the PCP2 and PCP3 proteins influence large molecular weight capsular polysaccharides and exopolysaccharides that currently cannot be resolved to the same level of clarity.…”
Section: Pcp Proteinsmentioning
confidence: 99%
“…Any model also needs to take into account the interchangeability of Wzz proteins (Klee et al, 1997;Murray et al, 2006). Specific functional domains have not been identified in Wzz so far, and it is apparent from in vivo genetic studies that individual residues throughout Wzz are important (Daniels & Morona, 1999;Franco et al, 1998;Klee et al, 1997).…”
Section: Introductionmentioning
confidence: 99%